The effect of some principles of civil proceedings during appealing the actions of compulsory enforcement bodies officials - Rapyan, Yuriy Kh. (Journal of the Belarusian State University. Law, 2024)
The author of the article examines the features of the operation of some functional principles of civil proceedings in cases of complaints against decisions, actions (inaction) of compulsory enforcement bodies officials, taking into account the public legal nature of this category of cases. The possibility of the parties to a dispute exercising their regulatory rights in the light of the principle of dispositivity is analysed. The desirability of personal participation of officials of compulsory enforcement bodies in court hearings in the studied category of cases is substantiated in order to implement the adversarial principles of the process and ensure the implementation of the principle of immediacy of the trial.
Keywords: principles of civil proceeding; complaint; bailiff; dispositivity; competitiveness; immediacy